Wild immunology assessed by multidimensional mass cytometry. Issue 1 (12th July 2016) - Japp, Alberto Sada; Hoffmann, Kerstin; Schlickeiser, Stephan; Glauben, Rainer; Nikolaou, Christos; Maecker, Holden T.; Braun, Julian; Matzmohr, Nadine; Sawitzki, Birgit; Siegmund, Britta; Radbruch, Andreas; Volk, Hans‐Dieter; et al.
Abstract: A great part of our knowledge on mammalian immunology has been established in laboratory settings. The use of inbred mouse strains enabled controlled studies of immune cell and molecule functions in defined settings. These studies were usually performed in specific‐pathogen free (SPF) environments providing standardized conditions. In contrast, mammalians including humans living in their natural habitat are continuously facing pathogen encounters throughout their life. The influences of environmental conditions on the signatures of the immune system and on experimental outcomes are yet not well defined. Thus, the transferability of results obtained in current experimental systems to the physiological human situation has always been a matter of debate. Studies elucidating the diversity of "wild immunology" imprintings in detail and comparing it with those of "clean" lab mice are sparse. Here, we applied multidimensional mass cytometry to dissect phenotypic and functional differences between distinct groups of laboratory and pet shop mice as a source for "wild mice". For this purpose, we developed a 31‐antibody panel for murine leukocyte subsets identification and a 35‐antibody panel assessing various cytokines. Established murine leukocyte populations were easily identified and diverse immune signatures indicative of numerous pathogen encounters were classified particularly in pet shop mice and to a lesser extent in quarantine and non‐SPF mice as compared to SPF mice. In addition, unsupervised analysis identified distinct clusters that associated strongly with the degree of pathogenic priming, including increased frequencies of activated NK cells and antigen‐experienced B‐ and T‐cell subsets. Our study unravels the complexity of immune signatures altered under physiological pathogen challenges and highlights the importance of carefully adapting laboratory settings for immunological studies in mice, including drug and therapy testing. © 2016 International Society for Advancement of Cytometry